The Role of Artificial Intelligence Dimensions on Accounting Information System Efficiency: Case Study of a Sharia Banking Company in Indonesia - Pinuji, Baskoro Suryo; Khomsiyah (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This study examines the role of artificial intelligence dimension in improving the efficiency of Accounting Information Systems in Islamic Banking Companies in Indonesia. In the era of the growing industrial revolution 4.0, the role of artificial intelligence is becoming the center of attention in various sectors and businesses. The development of artificial intelligence technology has had a significant impact on the way financial information is processed, managed, and used in decision making. This study aims to analyze in depth the application of artificial intelligence dimensions in the realm of accounting and identify the relationship to the efficiency of Accounting Information Systems. The results of this study are expected to provide important knowledge about the role of artificial intelligence technology in the context of accounting, as well as provide guidance for accounting and technology practitioners to optimize the use of artificial intelligence in improving the efficiency of Accounting Information Systems. By examining 34 respondents from 19 Islamic Banking Companies in Indonesia, the study found that the dimension of machine learning has a positive effect on the efficiency of accounting information system. However, this study did not find a positive effect of expert system dimension and knowledge representation and inference dimension on accounting information system efficiency.